RETENTION OF REMOTE PUBLIC HEALTH CENTER DOCTOR IN NORTH KONAWE DISTRICT - Sondang Whita Kristina Tambun; Masyitoh Bashabih (Jurnal Administrasi Kesehatan Indonesia)
Background: Remote public health centers (PHCs) have the highest proportion of PHCs without doctors, with Southeast Sulawesi Province ranking fifth in this regard. PHCs serve as the main gateway to health services in rural and remote areas. Despite its high fiscal capacity and provision of support for medical education and incentives, North Konawe District has not succeeded in retaining doctors in its public health centers.